Featured Article: Temporal responses of human endothelial and smooth muscle cells exposed to uniaxial cyclic tensile strain - Greiner, Alexandra M.; Biela, Sarah A.; Chen, Hao; Spatz, Joachim P.; Kemkemer, Ralf (Experimental biology and medicine, 2015)
The physiology of vascular cells depends on stimulating mechanical forces caused by pulsatile flow. Thus, mechano-transduction processes and responses of primary human endothelial cells (ECs) and smooth muscle cells (SMCs) have been studied to reveal cell-type specific differences which may contribute to vascular tissue integrity. Here, we investigate the dynamic reorientation response of ECs and SMCs cultured on elastic membranes over a range of stretch frequencies from 0.01 to 1 Hz. ECs and SMCs show different cell shape adaptation responses (reorientation) dependent on the frequency. ECs reveal a specific threshold frequency (0.01 Hz) below which no responses is detectable while the threshold frequency for SMCs could not be determined and is speculated to be above 1 Hz. Interestingly, the reorganization of the actin cytoskeleton and focal adhesions system, as well as changes in the focal adhesion area, can be observed for both cell types and is dependent on the frequency. RhoA and Rac1 activities are increased for ECs but not for SMCs upon application of a uniaxial cyclic tensile strain. Analysis of membrane protrusions revealed that the spatial protrusion activity of ECs and SMCs is independent of the application of a uniaxial cyclic tensile strain of 1Hz while the total number of protrusions is increased for ECs only. Our study indicates differences in the reorientation response and the reaction times of the two cell types in dependence of the stretching frequency, with matching data for actin cytoskeleton, focal adhesion realignment, RhoA/Rac1 activities, and membrane protrusion activity. These are promising results which may allow cell-type specific activation of vascular cells by frequency-selective mechanical stretching. This specific activation of different vascular cell types might be helpful in improving strategies in regenerative medicine.